The management of bilateral myelolipoma: Case report and review of the literature. (2015) - Zattoni, Davide; Balzarotti, Ruben; Rosso, Raffaele
Highlights: The adrenal myelolipoma is a rare benign tumor of the adrenal gland. In some cases, they can be found bilaterally. Symptomatic tumors or those bigger than 7 cm are usually treated surgically. Small adrenal myelolipomas (< 7 cm) and asymptomatic ones can be managed conservatively. These neoplasms are benign and at low risk of rupture and whenever possible the endocrine function must be preserved. Abstract: Introduction: Bilateral adrenal myelolipoma is a rare benign neoplasm. We presented the case of a young man affected by a bilateral myelolipoma and the analysis of the literature of bilateral cases of myelolipoma. Our purpose is to give a suggestion of clear terms of reference regarding the management of this kind of bilateral neoplasm. Presentation of case: We reported the case of a 41-year-old healthy man complained of abdominal pain in the upper quadrants. No significant alterations were found in routine blood and endocrinological tests. The imaging (CT and MRI) showed a huge right adrenal mass and a smaller lesion at the left adrenal gland. The preoperative pathological characterization was suggestive for a myelolipoma. A right open adrenalectomy was performed, and a radiological surveillance was planned for the left tumor. The pathological exam confirmed the diagnosis. Discussion: In literature, there are 36 cases described. The clinical presentation consisted of symptomatic tumors, incidentally diagnosed lesions or myelolipomas in patients with an associated endocrinal disorder. Symptomatic tumors or those bigger than 7 cm, because of the potential risk of rupture, are usually treated surgically. In smaller (<7 cm) and asymptomatic ones the surgical treatment is not univocal. Conclusion: In the setting of the surgical treatment, it is important to preserve in some way the hormonal function. For that reason, the bilateral adrenalectomy has to be reserved for symptomatic or sizeable (>7 cm) cases. As far as we know, this is the first review on bilateral myelolipomas.